Evaluation of spot urine albumin creatinine ratio as a screening tool for prediction of preeclampsia - Sirsam, Shyamkumar; Chavan, Snehal S.; Chavan, Rohidas (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Preeclampsia is the second leading cause of maternal mortality, accounting for approximately 12-18% of pregnancy-related deaths. Spot urine albumin creatinine ratio (UACR) underscores its significance as a practical tool for earlier detection and effective management thereby enhancing clinical outcomes for both mother and their infants. Methods: Singleton pregnant women between 16 and 20 weeks of gestation attending the antenatal care (ANC) outpatient department (OPD) of GMC Akola were enrolled in this prospective study. The spot urinary albumin-to-creatinine ratio (UACR) was calculated for each case. All patients were placed under regular follow-up at 24 weeks, 28 weeks, 32 weeks, 34 weeks, 36 weeks, and subsequently on a weekly basis until delivery. Special attention was given to identifying the development of preeclampsia during the antenatal period and/or at the time of delivery. Results: A UACR cutoff of 35.5 mg/mmol was identified as predictive of preeclampsia, with a significant association noted (p<0.0001). Diagnostic performance measures revealed a sensitivity of 85.1%, specificity of 91.4%, PPV of 82.6%, and NPV of 92.8%, suggesting high diagnostic accuracy. Conclusions: The present study establishes that spot UACR, when measured between 16-20 weeks of gestation in asymptomatic pregnant women, serves as a highly sensitive and specific early screening tool for predicting the subsequent development of preeclampsia.